Analysis of MUI Office Security System Using Routine Activity Theory: Case Study of Shooting at MUI Office - Kurniawati, Deni; Sukabdi, Zora A.; Wardhana, I Made Wisnu (Journal of Law, Politic and Humanities, 2025)
The shooting incident at the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) office has raised public concern regarding the security systems of religious institutions in Indonesia. This study aims to analyze the security system of the MUI office using the Routine Activity Theory (RAT), which emphasizes three key elements for the occurrence of crime: a motivated offender, a suitable target, and the absence of a capable guardian. Employing a case study approach and qualitative methods, data were collected through document analysis, media reports, and interviews with relevant stakeholders. The findings reveal that weaknesses in surveillance and the lack of technology-based security systems contributed to the incident. These results highlight the urgency of upgrading security measures, including enhancing the capacity of security personnel, installing electronic surveillance systems, and establishing more adaptive standard operating procedures (SOPs) to respond to potential threats. This study contributes to the development of crime